(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2020)
The main aim of this paper is to discuss the usage of cloud storage services, enabling individuals to store their information in the cloud and keep away from the local data storage and maintenance expense. Numerous data integrity auditing systems have been implemented to guarantee the quality of the data stored in the cloud. An individual would like to enroll his private key to create the authenticators for understanding the auditing of data integrity in certain, but not all of the current system. The user must then have a hardware token (e.g. USB token, smart card) for storing the private key and memorizing a password to trigger the private key. Most of the new data integrity auditing system will be unable to operate if the user misplaced this hardware token or forgot this password. We are proposing a new module called data integrity auditing without private key storage to solve this issue, and developing such a scheme using block chain technology. In this project we are proposing a computerized signature along with face reorganization with block chain operation, so that there will be no unique design to obtain unauthorized and furthermore to prevent hacking operation and all the respective user data or information will be stored in cloud with maximum security.